Isu Sosio-Historis dalam Tafsir Al-Qur’an Al-Karim - Ahmad Nabil Amir; Tasnim Abdul Rahman (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2022)
This paper discusses political and social issues in kitab Tafsir al-Qur’an al-Karim penned by al-Ustaz H. A. Halim Hasan, H. Zainal Arifin Abbas dan Abdur Rahim Haitami. Kitab Tafsir al-Qur’an al-Karim by these trio scholars was among the pre-eminent works of contemporary tafsir in Indonesia acclaimed for its balanced method of commentary using transmitted narrative (al-naql) and rational judgement (al-‘aql) in commentary. Some crucial issues of politics addressed were justice, democracy, shura (consultation) and freedom while social issues treated were hypocrisy, history of the Children of Israel, prophethood, natural disposition, intercession, mysticism and arrangement of nature. The method was descriptive and analytical in highlighting political and social views brought forth in the Tafsir. The finding shows that the political and social issues addressed in this work have been significantly established. The accomplishment has positive implication in the development and reform of tafsir in modern times that critically assist in the religious movement for social justice and political reform in Indonesia.